2022
DOI: 10.1177/00037028221131577
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Carcinoembryonic Antigen Surface-Enhanced Raman Spectroscopy (SERS) Aptamer Sensor Based on the Silver Nanorod Array Chip

Abstract: Carcinoembryonic antigen (CEA) is a cancer-related tumor marker, and it is important to develop a sensitive CEA detection technique. In this paper, a SERS-aptamer sensor for carcinoembryonic antigen (CEA) was based on thiol aptamer and phenylboronic acid. CEA thiol aptamer (Aptamer-SH) modified silver nanorod array chip was used as the SERS capture substrate. 4-Mercaptophenylboronic acid (4-MPBA) modified Ag NPs was used as SERS tags (Ag@4-MPBA). The affinity of the aptamer with CEA was used to ensure the sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…When combined with the specificity and versatility (here, Raman-active labeling) of nucleic acid aptamers, the technique was able to reach low limits of detection (that could challenge the limits of PCR techniques) as shown for SARS-CoV-2 [163,164] as well as the influenza A virus [165,166]. SERS was also applied recently for the sensitive detection of cancer biomarkers, such as carcinoembryonic antigen (CEA) [167]. In particular, Zhang et al have shown valuable improvement in the utilization of SERS through the detection of cancer cell-derived exosomes in clinical serum samples [168].…”
Section: Optical Aptasensorsmentioning
confidence: 99%
“…When combined with the specificity and versatility (here, Raman-active labeling) of nucleic acid aptamers, the technique was able to reach low limits of detection (that could challenge the limits of PCR techniques) as shown for SARS-CoV-2 [163,164] as well as the influenza A virus [165,166]. SERS was also applied recently for the sensitive detection of cancer biomarkers, such as carcinoembryonic antigen (CEA) [167]. In particular, Zhang et al have shown valuable improvement in the utilization of SERS through the detection of cancer cell-derived exosomes in clinical serum samples [168].…”
Section: Optical Aptasensorsmentioning
confidence: 99%
“…As such, identifying the CEA levels holds significant clinical value in tumor diagnosis. Various sensing approaches have been suggested for CEA detection and monitoring, including fluoroimmunoassay, enzyme-linked immunosorbent assay (ELISA), Raman spectroscopy, radioimmunoassay, and surface plasmon resonance . However, target detection following such sensing approaches commonly requires long processing times, expensive instruments, and labeled markers .…”
Section: Introductionmentioning
confidence: 99%